Carbon films as perfect electromagnetic wave absorbers and anti‐reflectors. (1st May 2017) - Batrakov, Konstantin; Paddubskaya, Alesya; Kuzhir, Polina
Abstract : It is shown that thin carbon coating with thicknesses, depending on its structure and porosity, ranging from tens of nanometres to tens of microns can absorb almost all incident microwave radiation without reflection. Special conditions on dielectric properties of substrate and conductivity of carbon material, which are necessary for the realisation of such a perfect absorber, are derived. The conductance of the carbon coating can then be controlled by proper porosity.